Mario Ridolfi – Intorno a Palazzo Spada a Terni - Cresci, Edoardo (Firenze Architettura, 2021)
In 1957 Mario Ridolfi drew up a variant to the Reconstruction Plan for Terni which involves the entire area of Corso del Popolo. From the land behind Palazzo Spada will emerge, over time, the Franconi Houses, the Pallotta Houses, the new facade of Palazzo Montani and the project for the New Municipal Offices Building. Constructions which will determine a new image of the city, composing together with it a single urban structure capable of taking on the renewed values that Terni needed.